The Impact of Whistleblowing Awards Programs on Corporate Governance - Austin, Janet; Lombard, Sulette (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2019)
Since the introduction of a whistle-blower awards program by the US Securities and Exchange Commission in 2010, securities regulators in other countries, including Canada, have adopted, or are considering adopting, similar programs. For example, in 2016, the Ontario Securities Commission adopted its own whistle-blower award program. Although the primary main reason for these programs is to encourage the reporting of securities violations to the regulator, they could also have an impact on corporate governance. This is because the implementation of such a program may prod companies to design, and then instigate, a more effective internal whistle-blowing system. A truly successful internal whistle-blowing system can enable a company to detect and correct potential wrongdoing before it causes significant harm. This article closely examines this connection between whistle-blowing award programs, companies’ compliance and risk management systems, and how a whistle-blowing award program might well result in more effective internal whistle-blowing systems without the need for a regulator to resort to the imposition of prescriptive rules. As such, this article reflects upon how whistle-blower award programs fit within new governance regulatory theory that challenges traditional “command-and-control-type”regulation in favour of an outcome-driven approach.